1983
DOI: 10.1161/01.hyp.5.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced NE uptake by isolated hypothalamic storage vesicles of hypertensive rats.

Abstract: The in vitro uptake of 3 H-NE by storage vesicles from the hypothalamus of age-matched spontaneously hypertensive rats (SHR) and Wistar-Kyoto (WKY) rats has been studied using a new reliable procedure for the isolation of biochemically active storage vesicles. In each of 13 paired studies, done in triplicate, storage vesicles of SHR took up more 3 H-NE than those of WKY. (The mean difference was 37% more uptake by SHR.) Electron-microscopic examination of normotensive samples showed a concentration of intact s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

1985
1985
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…First, based on our previous observations described earlier, we investigated whether CA in SHR may be stored and released differently. This hypothesis was supported by previously published evidence of morphological changes in storage vesicles in SHR and their increased ability to take-up 3 H-NA (Rho et al 1983), higher expression of norepinephrine transporter in SHR brainstem cultures (Veerasingham et al 2005) and increased tyrosine hydroxylase expression in the SHR ventrolateral medulla (Reja et al 2002). We therefore reasoned that the structural differences in CA-storing vesicles and/or NA synthesis and transport could translate into enhanced packaging and release of CA in SHR.…”
Section: Altered Central Noradrenalin Signalling In An Animal Model Of Essential Hypertensionsupporting
confidence: 71%
“…First, based on our previous observations described earlier, we investigated whether CA in SHR may be stored and released differently. This hypothesis was supported by previously published evidence of morphological changes in storage vesicles in SHR and their increased ability to take-up 3 H-NA (Rho et al 1983), higher expression of norepinephrine transporter in SHR brainstem cultures (Veerasingham et al 2005) and increased tyrosine hydroxylase expression in the SHR ventrolateral medulla (Reja et al 2002). We therefore reasoned that the structural differences in CA-storing vesicles and/or NA synthesis and transport could translate into enhanced packaging and release of CA in SHR.…”
Section: Altered Central Noradrenalin Signalling In An Animal Model Of Essential Hypertensionsupporting
confidence: 71%
“…Higher output from large events was a combination of their much higher transmitter load (≈270%) and higher frequency relative to WRs. Increase in the size of these events may be because of a higher norepinephrine transporter activity in the SHR brain stem7; an increased expression of tyrosine hydroxylase, the key enzyme of NA/ADR biosynthesis, in the SHR ventral medulla,44; and/or alterations in the vesicular storage apparatus 6. These changes, when combined, possibly alter the way the vesicles are formed or filled.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is based on evidence of morphological changes in storage vesicles in SHRs and their increased ability to take up 3 H-NA,6 higher expression of norepinephrine transporter in SHR brain stem cultures,7 and increased tyrosine hydroxylase expression in the SHR ventrolateral medulla 8. Structural differences in NA-storing vesicles and/or NA synthesis and transport could translate into enhanced packaging and release of catecholamine (CA) in SHRs.…”
mentioning
confidence: 99%
“…Vesicle properties Interestingly, NA storage vesicles may be structurally and/or biochemically altered in SHR. It was reported that storage vesicles of SHR took up 37% more [ 3 H]NA than those of WKY rats and the speed of uptake was also significantly faster (Rho et al 1983). At the electron microscopic level, WKY rats displayed intact, largely well‐delineated dense‐cored vesicles, while in SHR these vesicles appeared swollen and distorted.…”
mentioning
confidence: 99%
“…At the electron microscopic level, WKY rats displayed intact, largely well‐delineated dense‐cored vesicles, while in SHR these vesicles appeared swollen and distorted. This raises the possibility that in SHR NA is stored and released from an altered pool of vesicles with, possibly, a different transmitter load and cotransmitter composition (Rho et al 1983).…”
mentioning
confidence: 99%